Al-Qadi's Poetic Wisdom as a Catalyst for the Sustainable Preservation of Saudi Arabia's Coffee Culture - Kurniawan Arif Maspul (Universitas Pahlawan Tuanku Tambusai, 2023)
This article embarks on a captivating journey that delves deep into the intricate relationship between the profound local wisdom expressed in the poetic works of Muhammad Abdullah Al-Qadi and the vibrant coffee culture of Saudi Arabia. Beyond being a beverage of cultural significance, coffee holds a pivotal role in shaping the sustainable future of Saudi Arabia's agricultural practices and cultural heritage. Al-Qadi's poetic masterpiece,